2015
DOI: 10.18632/oncotarget.5793
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of HER2-retargeted oncolytic-HSV by mesenchymal stromal cells protects from lung and brain metastases

Abstract: Fully retargeted oncolytic herpes simplex viruses (o-HSVs) gain cancer-specificity from redirection of tropism to cancer-specific receptors, and are non-attenuated. To overcome the hurdles of systemic delivery, and enable oncolytic viruses (o-viruses) to reach metastatic sites, carrier cells are being exploited. Mesenchymal stromal cells (MSCs) were never tested as carriers of retargeted o-viruses, given their scarse-null expression of the cancer-specific receptors. We report that MSCs from different sources c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…Attributed to their innate tumor tropism, stem cells carrying oHSV have been shown to target tumor lesions in the lung and prevent metastases upon i.v. injection (43). Based on previous findings and our present findings, stem cell-based oncolytic virotherapies could have the potential to be broadly applicable in targeting metastatic lesions in organs such as the liver, colon, and lung.…”
Section: Ifnγsupporting
confidence: 77%
See 1 more Smart Citation
“…Attributed to their innate tumor tropism, stem cells carrying oHSV have been shown to target tumor lesions in the lung and prevent metastases upon i.v. injection (43). Based on previous findings and our present findings, stem cell-based oncolytic virotherapies could have the potential to be broadly applicable in targeting metastatic lesions in organs such as the liver, colon, and lung.…”
Section: Ifnγsupporting
confidence: 77%
“…Recent studies have shown that i.v. injected MSC-oHSV have therapeutic efficacy in treating lung metastatic tumors (43). These studies imply that i.v.-injected MSC-oHSV would be more suitable for treating both primary and metastatic tumors in the lungs as opposed to the tumors in the brain.…”
Section: Discussionmentioning
confidence: 92%
“…R-LM249 exerted a therapeutic effect against peritoneal and brain metastases of ovarian and breast cancers after intra-peritoneal injections [ 55 ]. R-LM249 can be administered systemically by means of carrier cells, and exerts therapeutic effects against lung and brain metastases [ 57 ]. The full retargeting observed in cell cultures holds true also in animals.…”
Section: Overview Of Tropism Retargeting Based On Modification Of mentioning
confidence: 99%
“…The use of mesenchymal stem cells as carriers of retargeted oncolytic viruses has not been attempted, likely because these cells exhibit scarse-null expression of the targeted receptors. Recently, we reported that mesenchimal stromal cells (MSCs) from different sources can be forcedly infected with an HER2-retargeted oncolytic HSV, by exposing the virion-MSC mixtures to the fusogenic agent PEG 6000 [ 57 ]. Progeny viruses spread from MSCs to cancer cells in vitro and in vivo .…”
Section: Systemic Delivery Of Retargeted Oncolytic Hsvs By Means Omentioning
confidence: 99%
See 1 more Smart Citation